(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article is devoted to the work of known Kazakh writer Didar Amantai. The object of research is the novel «Flowers and books». The author analyses the functions and value of dreams in work of the writer. The symbolics of the images represented by the author reveals. Much attention is spared to the content of images. In the article interpretation of the basic images arising in dreams of heroes is given. The author comprehensively and deeply investigates the novel, revealing skill of the writer, his skill to get into the essence of the phenomenon represented by him. Every image, each detail become meaningful in work. The author of article emphasizes symbolics of the title of the novel, reflection of ideas of the writer in dreams of the hero. At the analysis of the novel «Flowers and books» the complex approach is used for allowing full and completely to open investigated problem.